Financial Inclusion among the Female Customers of Microfinance: An Evidence from Pokhara Metropolis - Susmita Subedi; Bharat Ram Dhungana (Journal of Development and Administrative Studies, 2024)
This paper aims to examine financial inclusion among the female customers of microfinance in Pokhara metropolis. The study employed quantitative research design with a descriptive approach. Primary data was collected through a structured questionnaire to microfinance clients in Pokhara. A convenience sampling method was used, and data was collected from 110 participants. The results revealed that microfinance products have not significantly impacted financial inclusion (β= 0.015, p= 0.879) among female customers in Pokhara. While most participants were middle-aged, married, and involved in business, their financial literacy levels were basic and it is positively correlated with financial inclusion (p=0.006) and socio-economic factors significantly impact financial inclusion (β = 0.254, p=0.007). Key factors influencing their choice of microfinance included collateral-free loans and immediate access to funds. The findings suggest that achieving effective financial inclusion requires a broader approach beyond microcredit alone. Financial literacy empowers people to make better financial choices and access formal financial services. Additionally, socio-economic factors, such as education and income stability, positively influence financial inclusion. To enhance financial inclusion, it is essential to provide affordable financial products, digital services, and convenient access to financial services.